IDEOLOGICAL AND EVALUATIVE FUNCTIONS OF NEWSPAPER DISCOURSE IN UZBEK AND ENGLISH MASS MEDIA - Fayyoza Kamolova Mirza qizi (Modern American Journals, 2026)
This article explores the ideological and evaluative functions of newspaper discourse in Uzbek and English mass media from a comparative perspective. Using discourse analysis and critical pragmatic approaches, the study examines how ideological positions and value judgments are constructed through lexical choices, evaluative markers, presupposition, and framing strategies. The analysis demonstrates that English newspapers tend to employ implicit ideological evaluation and indirect stance-taking, while Uzbek media more frequently rely on explicit evaluation and socially oriented judgments. The findings reveal both universal and culture-specific mechanisms of ideological representation in newspaper discourse.
Keywords: newspaper discourse, ideology, evaluative language, media discourse, mass media, discourse analysis, ideological functions, evaluative functions, Uzbek and English, comparative linguistics